2018
DOI: 10.1016/j.exer.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Vergence driven accommodation with simulated disparity in myopia and emmetropia

Abstract: The formation of focused and corresponding foveal images requires a close synergy between the accommodation and vergence systems. This linkage is usually decoupled in virtual reality systems and may be dysfunctional in people who are at risk of developing myopia. We study how refractive error affects vergence-accommodation interactions in stereoscopic displays. Vergence and accommodative responses were measured in 21 young healthy adults (n=9 myopes, 22-31 years) while subjects viewed naturalistic stimuli on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 122 publications
1
26
0
Order By: Relevance
“…Further investigation is needed to examine how these changes interact with other factors in the development of myopia, such as the amount of time spent performing near vision tasks as well as variability in accommodation state and consequent defocus. Our group has recently shown that individuals with myopia have more variable accommodation responses than emmetropes (Maiello, Kerber, Thorn, Bex, & Vera-Diaz, 2018 ). The relationship between spatiotemporal visual sensitivity and environmental factors in eye growth also warrants further research as animal models show a significant effect of the temporal modulation of light in axial elongation and the development of induced myopia (Crewther, Barutchu, Murphy, & Crewther, 2006 ; Di, Liu, Chu, Zhou, & Zhou, 2013 ; Lan, Feldkaemper, & Schaeffel, 2014 ; Rucker et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation is needed to examine how these changes interact with other factors in the development of myopia, such as the amount of time spent performing near vision tasks as well as variability in accommodation state and consequent defocus. Our group has recently shown that individuals with myopia have more variable accommodation responses than emmetropes (Maiello, Kerber, Thorn, Bex, & Vera-Diaz, 2018 ). The relationship between spatiotemporal visual sensitivity and environmental factors in eye growth also warrants further research as animal models show a significant effect of the temporal modulation of light in axial elongation and the development of induced myopia (Crewther, Barutchu, Murphy, & Crewther, 2006 ; Di, Liu, Chu, Zhou, & Zhou, 2013 ; Lan, Feldkaemper, & Schaeffel, 2014 ; Rucker et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Employing simulated peripheral dioptric blur in richer, naturalistic training environments may help counteract the adverse effects of vergence-accommodation conflicts 102 . Refractive error is also linked to stronger vergence-accommodation conflicts 119 , which may have implications particularly for anisometropic strabismic patients who may have different refraction in the two eyes. In recent work however we have demonstrated a synergistic link between eye and hand movements in 3D, which persists even with simulated asymmetric visual impairment 103 .…”
Section: Strengthening the Effects Of Oculomotor Trainingmentioning
confidence: 99%
“…It should be noted that the study sample presents a trend toward to myopia (-0.79 [1.39] D), and recent evidence suggests that the vergence in myopes is slower, while the accommodation is less stable in comparison to emmetropes. 65 In addition, there is evidence about the influence of the optical correction method on the accommodative and vergence demands while viewing oscillatory targets, with myopes demonstrating greater accommodative and vergence requirements when wearing soft contact lenses in comparison to spectacles. 23 The use of soft contact lenses permit to maintain the optical centre in a correct position at all viewing distances (soft contact lens moves with the eye), whereas spectacle correction is normally centred at far distance and it is used for all viewing distances.…”
Section: A Plausible Explanation For the Present Findingsmentioning
confidence: 99%